Analysis of the Influence of Communication on Employee Performance at the Lubuk Pakam Pratama Tax Service Office - Imelda Mestikawaty Sihombing; Vonna Safitry; Rika Juliana; Doli Sukma Manurung; Lasro Supiatman Siahaan (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the influence of communication on employee performance at the Lubuk Pakam Primary Tax Service Office. The research method used is quantitative with a simple linear regression approach. The study population consisted of 119 employees, with a sample of 54 people taken using non-probability sampling technique and the Slovin formula. Data were collected through questionnaires using a Likert scale and analyzed using validity, reliability, and hypothesis testing. The results showed that communication has a positive and significant effect on employee performance. This is evidenced by the t-count value of 7.255 > t-table 2.006 and a significance value of 0.000 < 0.05. The regression equation Y = 15.234 + 0.682X indicates that every one-unit increase in communication will increase employee performance by 0.682 units. The coefficient of determination (R²) of 0.507 indicates that communication contributes 50.7% to employee performance, while the rest is influenced by other factors. Thus, the better the communication within the office environment, the higher the employee performance.